ANALISA KEPASTIAN PERHITUNGAN TIAP AHLI WARIS DENGAN MENGGUNAKAN METODE CERTAINTY FACTOR - Muhammad Manarul Hidayat; Dian Asmarajati; Muslim Hidayat (Tekompedia : Jurnal Ilmiah Ilmu Komputer, 2024)
In general, Muslims do not understand the procedures for dividing and calculating inheritance, and the difficulty of finding experts in the field of inheritance according to Islamic law (Faraidh). This is a problem for Muslim communities, especially for heirs who wish to divide the inheritance according to Islamic law. The author uses the certainty factor method in designing expert systems. As a result of this research, an expert system for inheritance distribution was developed which can be used by the general public to solve problems of calculating and dividing inheritance.